Dyslipidemia correction with atorvastatin in patients with coronary heart disease and arterial hypertension - N. B. Amirov; M. V. Potapova; F. I. Ishkineev; G. V. Tukhvatullina; N. G. Efimova; L. F. Mingazutdinova (Кардиоваскулярная терапия и профилактика)
Aim. To assess atorvastatin lipid-lowering effect and tolerability at the initial stage of lipid-lowering treatment. Material and methods. The study included 47 patients (14 women, 33 men; mean age 55,6±11,6 years). Inclusion criteria were: verified coronary heart disease, CHD (stable effort angina, post-infarction cardiosclerosis), total cholesterol (TCH) level >5,0 mmol/l, low-density lipoprotein (LDL) CH level >3,0 mmol/l, triglycerides (TG) level _<3,5 mmol/l. CHD was verified in 31 patients (62%), including 17 with previous myocardial infarction (MI); 38 participants (76%) had arterial hypertension, 30 (60%) were overweight. All patients received atorvastatin (10 mg/d), individuals with CHD also received clopidogrel (75 mg/d). The follow-up period lasted for one month. After 14 days and one month of the therapy, lipid profile and liver function tests (LFT) were performed. Results. Thirty-day lipid-lowering therapy resulted in decreased TCH level (by 33,2%; p<0,01), reduced LDL-CH concentration (by 33,9%; p<0,05), elevated high-density lipoprotein (HDL) CH level (by 18,5%; p<0,05), and decreased atherogenicity index (by 38,4%; p<0,05). During one-month follow-up, no significant changes in LFT were observed. Conclusion. As early as during the first month of the treatment, lipid-lowering therapy with atorvastatin resulted in significant reduction in TCH, LDL-CH, and TG concentrations, together with increase in HDL-CH level. No effect on FLT was observed.